The Combination of Diabetic Foot Exercises and Warm Water Foot Soak for Unstable Blood Glucose Levels Nursing Problems in Elderly - Agustina, Liana Putri; Kurdi, Fahruddin; Ardhani, Ni Ketut (Al-Hijrah Indonesia, 2025)
Diabetes mellitus is a vital health disease to pay attention to in the elderly population. When compared to individuals without diabetes, the older adult with DM loses muscle mass faster and has more comorbidities such as hypertension. Another common complication of diabetes is diabetic neuropathy, which causes tingling and numbness in the extremities. One method for managing diabetes is to combine diabetes foot exercises with a warm water foot soak. This study aimed to see how diabetic foot exercises and warm water foot soak affected blood glucose levels and foot sensitivity in the older adult with diabetes. This research was a case study, and the research subject was an older adult with diabetes mellitus. Random blood glucose levels and foot sensitivity were measured using a glucometer and monofilament test. Client’s average blood glucose levels decreased from 239.25 mg/dL to 235.75 mg/dL. Foot sensitivity points have increased from 8 points on the right foot and 7 points on the left foot to 9 points on the right foot and 8 points on the left foot. A combination of diabetic foot exercises and warm water foot soak can reduce blood glucose levels and increase the sensitivity of the feet of older adults with diabetes. The combination of these two therapies can be complementary to pharmacological therapy for older adults with diabetes.